A first assessment of the sources of isoprene and monoterpene emissions from a short-rotation coppice Eucalyptus gunnii bioenergy plantation in the United Kingdom. (1st October 2021) - Purser, Gemma; Drewer, Julia; Morison, James I.L.; Heal, Mathew R.
Abstract: Eucalyptus gunnii is a fast-growing, cold-tolerant tree species endemic to Tasmania that is suitable for growing as short-rotation coppice (SRC) plantations in the UK. Fast growing eucalypts such as E. gunnii could potentially deliver higher biomass yields with a superior calorific value for the domestic bioenergy market than other SRC plantation species such as willow or poplar. However, eucalypts are known emitters of biogenic volatile organic compounds (BVOC) like isoprene and monoterpenes. These compounds contribute to the formation of atmospheric pollutants such as ozone and secondary organic aerosols. An assessment of the sources of BVOCs during the lifecycle of a UK E. gunnii SRC plantation found the mean standardised emissions of isoprene and total monoterpenes from branches of juvenile foliage to be 7.50 μg C gdw −1 h −1 and 1.30 μg C gdw −1 h −1, respectively. The predominant monoterpene emitted was cis-β-ocimene. Isoprene emissions from the forest floor were extremely low but monoterpene emissions peaked at 50 μg C m −2 h −1 . α-Pinene and d-limonene were the major components of the monoterpene emissions, with higher emissions correlated to the abundance of leaf litter. Both the magnitude and composition of monoterpene emissions from the forest floor varied during the SRC plantation life cycle, with the coppiced and regrowth stands of eucalyptus producing less emissions. The woodchip produced at harvesting emitted only trace levels of isoprene but substantial monoterpene emissions, up to 90 μg C m −2 h −1, predominately eucalyptol. Harvesting and resulting biomass chips may provide a short-lived concentrated source of BVOCs in winter at SRC plantations. Modelled annual emissions using MEGAN 2.1 (canopy emissions only) suggest that BVOC emissions from a UK E. gunnii SRC plantation are most abundant in summer, and that modelled annual isoprene and total monoterpenes emissions could be around 6.9 kg C ha −1 and 2.4 kg C ha −1 respectively, for a young plantation. Based on the very limited data, the per-hectare E. gunnii isoprene emissions are smaller than estimates for other SRC/SRF plantation species in the UK; the per-hectare monoterpene emissions are in the span of estimates for other plantation species. Highlights: First data for emissions of speciated BVOC from a UK eucalypt bioenergy plantation Isoprene emission from juvenile foliage six times greater than monoterpene emission cis-β-Ocimene and α-phellandrene major monoterpenes from juvenile foliage Forest floor monoterpene emissions smaller than branches and vary with lifecycle α-Pinene and d-limonene dominate forest floor emissions; eucalyptol from woodchip